Prostaglandin E(2)–prostoglandin E receptor subtype 4 (EP4) signaling mediates UV irradiation-induced systemic immunosuppression - Soontrapa, Kitipong (National Academy of Sciences, 2011)
UV radiation induces systemic immunosuppression. Because nonsteroidal anti-inflammatory drugs suppress UV-induced immunosuppression, prostanoids have been suspected as a crucial mediator of this UV effect. However, the identity of the prostanoid involved and its mechanism of action remain unclear. Here, we addressed this issue by subjecting mice deficient in each prostanoid receptor individually or mice treated with a subtype-specific antagonist to UV irradiation. Mice treated with an antagonist for prostaglandin E receptor subtype 4 (EP4), but not those deficient in other prostanoid receptors, show impaired UV-induced immunosuppression, whereas administration of an EP4 agonist rescues the impairment of the UV-induced immunosuppression in indomethacin-treated mice. The EP4 antagonist treatment suppresses an increase in the number of CD4(+)/forkhead box P3-positive (Foxp3(+)) regulatory T cells (Treg cells) in the peripheral lymph nodes (LNs) and dendritic cells expressing DEC205 in the LNs and the skin after UV irradiation. Furthermore, the EP4 antagonist treatment down-regulates UV-induced expression of receptor activator of NF-κB ligand (RANKL) in skin keratinocytes. Finally, administration of anti-RANKL antibody abolishes the restoration of UV-induced immunosuppression by EP4 agonism in indomethacin-treated mice. Thus, prostaglandin E(2) (PGE(2))–EP4 signaling mediates UV-induced immunosuppression by elevating the number of Treg cells through regulation of RANKL expression in the epidermis.